Chronic ethanol consumption increases the fragility of rat pancreatic zymogen granules. Issue 10 (October 1994) - Haber, P S; Wilson, J S; Apte, M V; Korsten, M A; Pirola, R C
Abstract : Intracellular activation of pancreatic digestive enzymes by lysosomal hydrolases is thought to be an early event in the pathogenesis of pancreatic injury. As ethanol excess is an important association of pancreatitis, experimental work has been directed towards exploring possible mechanisms whereby ethanol may facilitate contact between inactive digestive enzyme precursors and lysosomal enzymes. The aim of this study was to find out if chronic ethanol administration increases the fragility of rat pancreatic zymogen granules. Sixteen male Sprague-Dawley rats were pair fed ethanol and control liquid diets for four weeks. Zymogen granule fragility was then assessed in pancreatic homogenate by determination of (a) latency and (b) per cent supernatant enzyme after sedimentation of zymogen granules. Amylase was used as a zymogen granule marker enzyme. Latency was significantly reduced in pancreatic homogenates of ethanol fed animals suggesting increased zymogen granule fragility. In support of this finding, there was a trend towards increased supernatant enzyme after ethanol feeding. In conclusion, administration of ethanol increases the fragility of pancreatic zymogen granules in the absence of morphological evidence of pancreatic injury. It is proposed that zymogen granule fragility may play an early part in the pathogenesis of alcoholic pancreatitis by permitting contact between digestive and lysosomal enzymes.